2017
DOI: 10.1097/inf.0000000000001547
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to Second-line Antiretroviral Therapy Among Adolescents in Copperbelt Province, Zambia

Abstract: Greater support is needed for ALHIV who are on second-line regimens. Interventions for older adolescents that bridge the gap between school years and young adulthood would be helpful. More research is needed on why ALHIV who start on efavirenz-based regimens are more likely to switch within this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…On a contrary to the current study, another Zambian study found that there was suboptimal adherence to cART mainly due to increase in age [18]. This could have been that as adolescents increase in age, they are expected to take up more gender roles and responsibilities in society.…”
Section: Adherence To Cartcontrasting
confidence: 99%
“…On a contrary to the current study, another Zambian study found that there was suboptimal adherence to cART mainly due to increase in age [18]. This could have been that as adolescents increase in age, they are expected to take up more gender roles and responsibilities in society.…”
Section: Adherence To Cartcontrasting
confidence: 99%
“…Sharing the success story from South Africa would help in promoting VS in SSA [23,24]. Of relevance, VS is consistent with timely switch of paediatric ART [25][26][27][28], taking into consideration orphanhood and patient age for adequate monitoring and interpretation of PVL [29,30]. While supporting the use of 2 consecutive PVLs to confirm VF, further VL repeats should be discouraged for children known to be adherent, so as to prevent accumulating resistant patterns [15,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the patients’ perspectives seem to be given little consideration in the adherence intervention development and implementation. It is therefore important to assess effectiveness of existing strategies from the perspectives of PLHIV taking ART in order to recommend and develop relevant and acceptable strategies to patients [ 44 , 45 ]. This is evidenced in a study conducted in Malawi which highlighted how critical it is for health programmers to prioritize adherence view points from patients as part of strengthening the clinical monitoring strategy used [ 46 ].…”
Section: Introductionmentioning
confidence: 99%